Reconnoitering the association between body mass index and oral health among elementary school children in Hyderabad, Telangana, India - Jagadeeswara Rao Sukhabogi; B R Chandra Shekar; I Venkata Ramana; G Satish Kumar; N Harita; G Annapoorna (Wolters Kluwer Medknow Publications, 2019)
Objective: To evaluate the association between body mass index (BMI) and oral health status among elementary school children in Hyderabad, Telangana, India. Materials and Methods: This cross-sectional study was conducted among elementary school children selected from government, private-aided and private-unaided schools in Hyderabad. A stratified cluster random sampling technique was used to select study participants. All parents were requested to be personally present on the day of examination. All eligible children were assembled in a hall and their height in inches and weight in kilograms were recorded by two calibrated investigators. The oral health status of children was assessed using a predesigned oral health assessment proforma. Plaque status was assessed using Sillness and Loe plaque Index and caries using decayed and filled teeth (dft) by a trained and calibrated investigator. Results: One hundred and seventy-one children (89 males and 82 females) were included in the present study. Mean plaque score was 1.4 ± 0.6 with no significant difference in the mean plaque score between children in three different categories of nutritional status (P = 0.07). Mean dft among primary teeth was 1.1 ± 1.1 with a significantly higher score among children who were malnourished (2.4 ± 0.9) compared to children who were overweight (0.9 ± 0.9) and normal (0.4 ± 0.6) (P < 0.001). Conclusion: BMI was negatively associated with caries experience in primary dentition with no association with plaque scores. Overweight children with malnutrition had significantly higher caries experience compared to children with normal BMI.